Pola Pertumbuhan Mikroba Dominan pada Fermentasi Alami Buah Jeruk Siam (Citrus nobilis) untuk Produksi Arak - Duma, Vony Christin Pato; Permana, I Dewa Gde Mayun; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i01.p08, 2025)
Awan Village is one of the abundant siamese orange (Citrus nobilis) producing villages in Kintamani District, Bangli Regency. The abundance of siamese orange is utilized by Awan Village by processing siam oranges into orange arak as an attempt to diversify citrus fruit products. Orange arak is one of the processed products of Kintamani siam oranges processed through a fermentation and distillation process. UMKM Tirta Kahuripan as an orange arak producer in Awan Village uses natural fermentation process for 21 days. Natural fermentation generally involves many types of microbes, but in natural fermentation of orange in the processing of arak, has been reported in various studies that the dominant microbes that are involved are yeast (Sacharomyces cereviseae), lactic acid bacteria, and acetic acid bacteria. The yeast contributes as alcohol-producing microbes, while lactic acid bacteria and acetic acid bacteria contribute to the formation of acids that affect the flavor of orange wine. Generally, the fermentation period of arak that made of nira is about three to five days. The aims of this study was to observe the growth pattern of dominant microbes during 21 days of natural fermentation of siamese orange fruit in the production of orange arak and the concentration of alcohol produced to obtain the right fermentation time to improve the quality of orange arak. This research is an exploratory study that done twice and the data were analyzed by interpreting the data through tables and graphs. The results showed that the yeast population was dominant on the 18th day of fermentation and the lowest on the 6th day. Lactic acid bacteria and acetic acid bacteria populations were dominant on day 10. The highest alcohol concentration was obtained on day 6 of fermentation at 4.04 percent. Keywords: acetic acid bacteria, growth pattern, lactic acid bacteria, siam orange, yeast